Engineered Ferritin for Magnetogenetic Manipulation of Proteins and Organelles Inside Living Cells. Issue 42 (28th September 2017) - Liße, Domenik; Monzel, Cornelia; Vicario, Chiara; Manzi, John; Maurin, Isabelle; Coppey, Mathieu; Piehler, Jacob; Dahan, Maxime
Abstract: Magnetogenetics is emerging as a novel approach for remote‐controlled manipulation of cellular functions in tissues and organisms with high spatial and temporal resolution. A critical, still challenging issue for these techniques is to conjugate target proteins with magnetic probes that can satisfy multiple colloidal and biofunctional constraints. Here, semisynthetic magnetic nanoparticles are tailored based on human ferritin coupled to monomeric enhanced green fluorescent protein (mEGFP) for magnetic manipulation of proteins inside living cells. This study demonstrates efficient delivery, intracellular stealth properties, and rapid subcellular targeting of those magnetic nanoparticles via GFP–nanobody interactions. By means of magnetic field gradients, rapid spatial reorganization in the cytosol of proteins captured to the nanoparticle surface is achieved. Moreover, exploiting efficient nanoparticle targeting to intracellular membranes, remote‐controlled arrest of mitochondrial dynamics using magnetic fields is demonstrated. The studies establish subcellular control of proteins and organelles with unprecedented spatial and temporal resolution, thus opening new prospects for magnetogenetic applications in fundamental cell biology and nanomedicine. Abstract : Magnetic manipulation of intracellular proteins is realized by designing semisynthetic magnetic nanoparticles based on the protein cage ferritin. Demonstrating efficient delivery, intracellular stealth properties, and rapid targeting of organelle structures, the magnetic nanoparticles are applied for the remote manipulation of targeted proteins, as well as for remote‐controlled reduction of mitochondrial dynamics.